2021
DOI: 10.1371/journal.pone.0251440
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review on biomedical journal peer review guides for reviewers

Abstract: Background Peer review is widely used in academic fields to assess a manuscript’s significance and to improve its quality for publication. This scoping review will assess existing peer review guidelines and/or checklists intended for reviewers of biomedical journals and provide an overview on the review guidelines. Methods PubMed, Embase, and Allied and Complementary Medicine (AMED) databases were searched for review guidelines from the date of inception until February 19, 2021. There was no date restriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 77 publications
0
20
0
1
Order By: Relevance
“…That said, the diversity of comments included in this section, and the fact that 51% of reviewers did not use the confidential comments area, suggests that journals might benefit from giving clearer guidance or training to their reviewer pool. Many journals provide guidance and checklists to reviewers, the contents of which were catalogued in a recent scoping review of biomedical journal peer review guides [7]. Unfortunately, this review did not report the number of guides that included content about how to use the confidential comments section, but may be worth exploring to understand the norms around use of this section and to help standardize language across peer review guides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That said, the diversity of comments included in this section, and the fact that 51% of reviewers did not use the confidential comments area, suggests that journals might benefit from giving clearer guidance or training to their reviewer pool. Many journals provide guidance and checklists to reviewers, the contents of which were catalogued in a recent scoping review of biomedical journal peer review guides [7]. Unfortunately, this review did not report the number of guides that included content about how to use the confidential comments section, but may be worth exploring to understand the norms around use of this section and to help standardize language across peer review guides.…”
Section: Discussionmentioning
confidence: 99%
“…However, the soundness of this approach has come into question as such masking may inadvertently encourage reviewers to be less conscientious about providing constructive and respectful feedback to authors [6]. To mitigate this concern, many journals provide guidelines for reviewers that set expectations for quality feedback [7,8]. In addition, to enhance transparency and accountability, some journals have an open peer-review process that either requires or gives reviewers the option to share their identity and/or make their review publicly available [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…Many journals provide guidance and checklists to reviewers, the contents of which were catalogued in a recent scoping review of biomedical journal peer review guides. [7] Unfortunately, this review did not report the number of guides that included content about how to use the confidential comments section, but may be worth exploring to understand the norms around use of this section and to help standardize language across peer review guides.…”
Section: Discussionmentioning
confidence: 99%
“…[6] To mitigate this concern, many journals provide guidelines for reviewers that set expectations for quality feedback. [7,8] In addition, to enhance transparency and accountability, some journals have an open peer-review process that either requires or gives reviewers the option to share their identity and/or make their review publicly available [4,9]. While such efforts to increase transparency are thought to improve review quality by increasing reviewers' sense of accountability, a series of studies conducted by the BMJ found no difference in the quality of masked versus unmasked peer reviews.…”
Section: Introductionmentioning
confidence: 99%
“…A quality assessment limitation will also be implemented during the search stage. Although quality or critical assessment of studies is not a scoping review requirement [ 56 , 57 ], some published scoping review protocols [ 68 , 69 ] and reviews [ 70 73 ] include such an assessment. Further, as one of the purposes of the proposed review is to identify gaps in the literature, quality assessment has been recommended in such situations [ 74 ].…”
Section: Methodsmentioning
confidence: 99%